Bone density unveiled: Investigating the effects of beta-thalassemia major on growing children and adolescents - Alam, Shah Jehan; Ahmed, Saleel; Ummara Siddique; Muhammad Asif; Syeda Komal Siraj; Arfa Khan (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate bone mineral density in children and adolescents with beta-thalassemia major. Method: The retrospective, cross-sectional, descriptive study was conducted from October 30 to November 15, 2024, at Peshawar General Hospital, Peshawar, Pakistan, and comprised data from January to August 2024 of paediatric beta-thalassemia major patients aged 2-18 years. Bone mineral density and Z-scores were evaluated using dual-energy X-ray absorptiometry scans of the lumbar spine, proximal femur and distal radius. Data was analysed using SPSS 25. Results: Of the 281 patients with mean age 6.92±3.74 years, 176(62.6%) were boys and 105(37.4%) were girls. The mean bone mineral density for proximal femur was 0.59±0.14g/cm², for lumbar spine 0.53±0.14g/cm²and for distal radius 0.35±0.09g/cm². Corresponding Z-scores were -0.41±1.81, -0.48±1.79, and -2.99±1.97. Low bone mass prevalence was 36(18.9%) at proximal femur, 43(16.4%) at lumbar spine, and 76(62.3%) at distal radius. Age negatively correlated with Z-scores at proximal femur (r=-0.27, p=0.001) and distal radius (r=-0.19, p=0.03). Male subjects had higher bone mineral density and Z-scores at the proximal femur than females(p=0.04). Conclusion: The reduction was significant in bone mineral density, particularly at the distal radius, in paediatric patients with beta-thalassemia major. The negative correlation between age and bone mineral density underscored the importance of early and continuous bone health monitoring in such patients. Key Words: Beta-thalassemia, Bone mineral density, Osteoporosis, Paediatric.